Analysis of Measured Drop Size Spectra over Land and Sea. (2nd October 2011) - Bumke Bumke, Karl Karl; Seltmann Seltmann, Jörg Jörg
Abstract : Drop size spectra were measured by using an optical disdrometer of type ODM 470 at different locations. They were subdivided in to four data sets: measurements over land, in coastal areas, over semienclosed seas, and over the open sea. Based on 1-minute measurement intervals, no differences were found in drop size spectra between continental and maritime areas. An exponential model with a rain rate depending on interception number and prefactor in the exponent fits well the spectra, and maximum drop sizes depend strongly on estimated rain rates. In contrast to other investigations, there are no significant differences between spectra of convective and stratiform rain based on 1-minute measurement intervals. However, spectra integrated over 10 minutes show the expected differences.